A Methodological Modeling of Emotion-Oriented Application in using Agent-Oriented Modeling - Syazwanie Filzah, Zulkifli (Universiti Malaysia Sarawak (UNIMAS), 2021)
Successful application nowadays requires the software engineer to consider the emotional needs of people. Emotion is intense feeling that are directed at someone, something or not at anything at all. It has been reported that the emotion consideration is needed to capture of what user want to feel and ensure all concern from users are into take consideration. Meanwhile, it has been indicated that capturing users’ emotional is needed for the acceptance of interactive application. Furthermore, considering the people feelings and emotions can uptake of interactive system, uncover new requirements and to improved system. Recent studies are not fully cover how to include emotional goal within the software development life cycle. Without proper guidance on how to incorporate user emotional goal within the software development life cycle, software engineers tend to ignore these goals as the project progresses to the next phase. Meanwhile, none of the technique proposed so far enables us to elicit user emotional goals. It is important to incorporate emotion thinking throughout the software development life cycle. In other words, how to elicitate user emotion, design the emotion-oriented application and implement it is yet to be explored. Based on these observations, it is sensible to claim that there was existing gap to fulfilling user emotional requirement throughout software development life cycle. Thus, this research bridge the gap to fulfill user emotional requirement by extending the initial works that claim the AOM can model the emotion-oriented application. This thesis introduces a systematic way to model an emotion-oriented application through Agent oriented Modeling (AOM). AOM is agentoriented methodology that is compliance with model driven architecture and uses the concept of agent in all stages of its process through modeling steps. In this thesis, the AOM is extended to guide the elicitate, analysis, design and implement of emotion-oriented application, a kind of interactive application. The extended AOM is evaluated in qualitative iv and quantitative manner through case studies of Quiz MASter. From the finding of the qualitative analysis, it showcases that extended AOM is useful for designer to systematically model an emotion-oriented application. All of the student believe the capability of AOM to model the emotion-oriented application. Meanwhile, the quantitative analysis can be concluded that the extended AOM is useful for students in producing emotion- oriented application systematically.